2021
DOI: 10.1007/s00192-021-04826-7
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of pelvic organ support defects in women undergoing pelvic organ prolapse surgery and compartment specific risk factors

Abstract: Introduction and hypothesis The objective of our study was to describe the distribution of pelvic organ prolapse (POP) in a population of women undergoing POP reconstructive surgery and to identify compartment-specific risk factors. Methods We conducted a retrospective observational study in a cohort of 326 women who underwent POP repair and had a standardized preoperative POP assessment using the Baden-Walker classification. The distribution of POP grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Knowing the distribution of defects can allow us to better adapt our repair techniques. We have shown in a series of 326 patients representing of a cohort of 1,811 women consulting for surgical correction of genital prolapse over a period of 20 years, that the anterior compartment is most frequently affected and often in association with the middle compartment ( 48 ). In this study we also showed that a previous hysterectomy increased the risk of developing posterior compartment prolapse.…”
Section: Pop Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing the distribution of defects can allow us to better adapt our repair techniques. We have shown in a series of 326 patients representing of a cohort of 1,811 women consulting for surgical correction of genital prolapse over a period of 20 years, that the anterior compartment is most frequently affected and often in association with the middle compartment ( 48 ). In this study we also showed that a previous hysterectomy increased the risk of developing posterior compartment prolapse.…”
Section: Pop Distributionmentioning
confidence: 99%
“…However, an increasing number of women prefer uterine preservation as it represents a symbol of femininity ( 12 , 13 ). Moreover, hysterectomy is probably an unnecessary act during POP surgery, and may increase the risk of posterior compartment prolapse ( 48 ). Recent studies also show a benefit of uterine preservation by reducing operating time and blood loss without affecting outcome ( 18 , 51 ).…”
Section: Hysteropreservation During Pop Surgerymentioning
confidence: 99%
“…Contemporary management of pelvic floor disorders involves not only the quantification of POP through measurement of organ points using reference lines but also more tailored and defect-specific treatment approaches that require imaging to deliver more detailed information on structural defects of the pelvic floor [ 27 ]. This customized treatment approach requires an improved understanding of the pathogenesis of POP through a sophisticated assessment of pelvic floor support structures.…”
Section: Discussionmentioning
confidence: 99%